Differences in sperm morphology in foam-nesting leptodactyline frogs (Anura, Leptodactylidae) - Salles, Natalia M. E. [UNESP]; Zara, Fernando J. [UNESP]; Prado, Cynthia P. A. [UNESP] (Wiley-Blackwell, 2017)
Sperm morphology is diverse among vertebrates and is influenced by the reproductive strategies adopted by species. In anurans, sperm morphology is associated with reproductive modes and mating systems. Here, we describe the sperm morphology of 11 frog species in the genus Leptodactylus and that of Lithodytes lineatus and discuss the relationship between sperm morphology and species' mating systems. We observed two distinct sperm morphotypes among the leptodactyline species, which differed mostly in head morphology. Type I sperm had triangular head, discrete acrosome vesicle with posterior margin not clearly visible; type II sperm had elongated head, clear acrosomal vesicle with posterior margin clearly visible. These sperm types do not seem to be associated with phylogeny; instead, type II sperm was observed in all polyandrous species analysed and in species with evidences of polyandry. Moreover, sperm of all species presented tail with undulating membrane connected to the axial fibre. We suggest that differences in sperm morphology might be associated with sperm competition to what polyandrous species are subjected. However, natural history observations on polyandrous mating in some species presenting type II sperm and phylogenetic comparative studies are need to elucidate the role of mating systems in the evolution of sperm morphology in leptodactylines.
Keywords: Amphibia; spermatozoon; mating system; ultrastructure